2022
DOI: 10.1186/s12887-022-03432-w
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ experiences with a home-based upper limb training program using a video coaching approach for infants and toddlers with unilateral cerebral palsy: a qualitative interview study

Abstract: Background Although early home-based upper limb training programs are promising, in-depth understanding of parents’ experiences with these programs is still limited. We developed an early home-based upper limb training program for infants and toddlers (8–36 months) with or at risk of unilateral cerebral palsy using video coaching for parents. The aim of this qualitative study was to evaluate parents’ experiences with the home-based training program using a video coaching approach in order to op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…This further highlights the need to communicate with families and individualize schedules to their needs. It has also been suggested in the literature to perform a comprehensive needs assessment prior to initiating therapy to identify and problem solve around issues that may arise with scheduling or intensive therapy (Verhaegh et al, 2022). This telehealth hybrid model worked well for both cases in the Infant CIMT Protocol because it was a one-hour session.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This further highlights the need to communicate with families and individualize schedules to their needs. It has also been suggested in the literature to perform a comprehensive needs assessment prior to initiating therapy to identify and problem solve around issues that may arise with scheduling or intensive therapy (Verhaegh et al, 2022). This telehealth hybrid model worked well for both cases in the Infant CIMT Protocol because it was a one-hour session.…”
Section: Discussionmentioning
confidence: 99%
“…This review reported that available evidence was limited to mostly qualitative research to date ( Knapp et al, 2023 ). Despite the small body of evidence, studies exploring the feasibility of telehealth home programs and effectiveness of parent coaching models in rehabilitation have demonstrated positive patient and caregiver feedback ( Beckers et al, 2020 ; Verhaegh et al, 2022 ). In addition, qualitative physical therapy research has reported benefits to hybrid models of care (a protocol with a combination of onsite and telehealth visits) in pediatrics that include improved patient communication, better understanding of the home environment and improved access to and continuity of care ( Hall et al, 2022 ).…”
mentioning
confidence: 99%
“…Buvo pastebėta, kad pagerėjo tėvų bendravimo įgūdžiai ir vaikų vystymasis. Įrodymai patvirtino tėvų ir tiesioginės specialisto intervencijos derinimą, siekiant kuo labiau pagerinti vaiko raidą [15]. P. Harniess ir bendraautoriai [5] teigia, kad bendrai specialistų ir tėvų sukurti tikslai ir namų programos (įskaitant mokomąją medžiagą) su realiais laiko įsipareigojimais, padeda tėvams patikėti ankstyvosios intervencijos įgyvendinamumu ir nauda.…”
Section: Diskusijaunclassified
“…Digitalization of paramedical treatments does not only take place in adult care but also in pediatric care, where communication about treatment primarily involves professionals and parents of underage patients. An example of a pediatric TET is the home-based upper limb training program using a video coaching approach for infants and toddlers with cerebral palsy (Verhaegh et al, 2022(Verhaegh et al, , 2023. In this treatment, interaction between paramedical professionals and parents of young patients takes place via a secure website.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on TET shows, among other things, that it is effective for the rehabilitation of very young children with this type of motor disability (Verhaegh et al, 2023) and that parents evaluate the treatment positively (Verhaegh et al, 2022). However, there is a lack of research addressing the interactional nature of TET and the impact of remoteness and use of technology on the interaction between professionals and parents.…”
Section: Introductionmentioning
confidence: 99%